Distance matters!: Evidence from professional team sports - Harald Oberhofer; Tassilo Philippovich; Hannes Winner (University of Innsbruck, Department of Public Finance, 2008)
This paper assesses the role of distance in professional team sports, taking the example of football (soccer). We argue that a team's performance in terms of scored and conceded goals decreases with the distance to the foreign playing venue. To test this hypothesis empirically, we investigate 6,389 away games from the German Football Premier League ('Erste Deutsche Bundesliga') between the playing seasons 1986-87 and 2006-07. We find that distance contributes significantly in explaining a guest team's propensity to concede goals, but not so for scoring goals. Focusing on the difference between scored and conceded goals ('goal difference') as a measure of the overall success of a football team, we observe a significant and non-monotonic impact of distance on team performance.
Keywords: L25; L83; C29; 330; professional team performance; distance; event count data; poisson regression model; Entfernung; Erfolgsfaktor; Fußballsport; Professioneller Sport; Regression; Schätzung; Deutschland